TECHNOLOGY OF DEVELOPMENT OF KNOWLEDGE OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS ON REPRODUCTIVE HEALTH - Abdunazarova Zulayxo Sharifkulovna (Scholar Express Journal, 2022)
Reproductive health is a state of complete physical, mental and social success not only in the absence of diseases and deficiencies, but also in the case of the reproductive system and all issues related to its functioning. Reproductive law is the recognition of the fundamental rights of all couples and individual persons to decide on the number of children, the space between them and the time of their birth, with a free and full responsibility, and the possession of the necessary information and Means for this. In this article, opinions and comments are made about the technologies for the development of students ' knowledge on reproductive health
Keywords: Higher education institution; students; reproductive health,; principles